Novel use of erector spinae plane block in laparoscopic surgery - Sandip Baheti; Cherukuri Kaushik; Sumedha Biswas (Indian Journal of Anaesthesia, 2022)
Background and Aims: Thoracic epidural and paravertebral blocks are gold standard analgesic techniques but they are associated with complications. Erector spinae plane (ESP) block is safer with comparable pain relief. ESP block is an established technique for postoperative pain relief. Its intraoperative use as an adjuvant to general anaesthesia (GA) is not yet known. The aim of this study was to assess the efficacy of ESP as an adjuvant to GA during laparoscopic surgery. Methods: This was a randomised controlled trial. Using a computer generated random number table, 50 patients were randomly allocated into two groups. Group G (n = 25) received GA and group GE (n = 25) received bilateral ESP (ultrasonography guided) block using 20 ml of 0.25% bupivacaine at the level of the transverse process of T6 before the induction of GA. Results: Group GE showed reduced requirement of fentanyl (P < 0.0001) and inhalational agents (P < 0.0001) with significant reduction in systolic blood pressure (P < 0.0001), diastolic blood pressure (P < 0.0001) and mean heart rate as compared to group G. Conclusion: ESP block is an easy, safe, excellent adjuvant to GA which reduces the requirement of analgesics and inhalational agents.